2018
DOI: 10.1186/s12947-018-0125-z
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic characteristics of primary malignant pericardial mesothelioma and outcomes analysis: a retrospective study

Abstract: BackgroundLittle is known about the echocardiographic characteristics of primary malignant pericardial mesothelioma (PPM) due to its rarity. The aim of this study was to explore the sex-specific echocardiographic patterns of PPM and risk factors for in-hospital mortality.MethodsA retrospective information retrieval was conducted for cases of PPM reported from China during 1981 and 2015. The diagnosis was made by histopathological examinations and only cases with echocardiographic descriptions were included. Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 21 publications
0
15
0
1
Order By: Relevance
“…In a recently published retrospective study, myocardial infiltration was reported in no <45% of all patients undergoing cardiac surgery for PPM. 9 We therefore suggest that myocardial infiltration by PPM, and thus potential limitations to cardiac surgery, should be considered even independent of imaging results, when therapeutic options are discussed. Analysis of pericardial fluid is also of limited value in most cases.…”
Section: Discussionmentioning
confidence: 97%
“…In a recently published retrospective study, myocardial infiltration was reported in no <45% of all patients undergoing cardiac surgery for PPM. 9 We therefore suggest that myocardial infiltration by PPM, and thus potential limitations to cardiac surgery, should be considered even independent of imaging results, when therapeutic options are discussed. Analysis of pericardial fluid is also of limited value in most cases.…”
Section: Discussionmentioning
confidence: 97%
“…Echocardiographic findings are also non-specific. They may show pericardial effusion, tamponade, thickening of the pericardium, or even a pericardial mass [ 3 ]. It further allows functional cardiac evaluation and the assessment of wall motion abnormalities [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…They may show pericardial effusion, tamponade, thickening of the pericardium, or even a pericardial mass [ 3 ]. It further allows functional cardiac evaluation and the assessment of wall motion abnormalities [ 3 ]. Magnetic resonance imaging and CT may prove useful in showing the degree of constriction and the extent of the tumor to the adjacent structures [ 2 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transthoracic echocardiography is the first-line diagnostic tool for pericardial tumors. However, echocardiography contains some limitations such as tissue characterization capability and restrict field of view in mediastinal and the right heart [6]. In human medicine, other noninvasive advance imaging modalities such as magnetic resonance imaging (MRI) and computed tomography (CT) have been applied to evaluate a cardiac tumor [7].…”
Section: Introductionmentioning
confidence: 99%